THE INFLUENCE OF ORGANIZATIONAL CLIMATE AND PROACTIVE PERSONALITY ON EMPLOYEE PERFORMANCE OF PT KREASI PUTRA HOTAMA - Hendrawan, Pendi; Basri, Muhammad; Kuswanti, Heni (Jurnal Edukasi Ekonomi, 2025)
This research aims to investigate influence of proactive personality and organizational atmosphere on the job performance of PT Kreasi Putra Hotama's startup staff. This research aims to investigate the impact of organizational climate and proactive personality on startup employee performance at PT Kreasi Putra Hotama. Specifically, it examines the individual effects of organizational climate and proactive personality on performance, as well as their combined effect. The study employs a quantitative cause-and-effect methodology. The study's population consisted of all employees who worked for PT Kreasi Putra Hotama, and a total sample of 26 people was obtained using the saturated sample technique. The data collection method involved disseminating a questionnaire via Google Forms. The findings reveal that: 1) There is a significant positive influence of the organizational climate on employee performance at PT Kreasi Putra Hotama, as evidenced by the calculated F value (2.622), which is greater than the critical t-table value (2.069) with a significance level of (0.005